Jatinder Verma’s Binglishing the British Stage. Tradaptation of Tartuffe as a case in point - Adamowicz-Pośpiech, Agnieszka (Studia Anglica Posnaniensia, 2025)
Scholars in the field of translation studies have underscored that the nature of drama translation is contingent upon the type of theatre for which it is intended. A notable example is found in intercultural theatre, where the objective of translation is not merely to acquaint the audience with a foreign text, but rather to tailor the source text to suit the cultural context of the target audience. This essay aims to scrutinise Jatinder Verma’s tradaptation of Tartuffe, performed for the intercultural Asian theatrical company Tara Arts in London. Verma adopted the term “tradaptation” (a fusion of “translation” and “adaptation”) from the French Canadian director Robert Lepage, signifying the integration of old texts into new cultural frameworks. The play Tartuffe is transposed to the seventeenth-century Indies under French colonisation, illustrating the enduring influence of religion and deceit on individuals. Verma’s selection of dramatic texts for performance was deliberate, consistently opting for plays that resonated with the contemporary socio-political landscape in Britain. This article delineates the rationale behind choosing Tartuffe and delves into the strategies employed to assimilate a foreign text, using it as a commentary on the prevailing political climate in Great Britain.